Genetic polymorphisms in innate immunity genes influence predisposition to tick-borne encephalitis - Fortova, Andrea; Barkhash, Andrey V; Pychova, Martina; Krbkova, Lenka; Palus, Martin; Salat, Jiri; Ruzek, Daniel (Journal of neurovirology, 2023)
Tick-borne encephalitis (TBE) is a neuroviral disease that ranges in severity from a mild febrile illness to a severe and life-threatening meningoencephalitis or encephalomyelitis. There is increasing evidence that susceptibility to tick-borne encephalitis virus (TBEV)-induced disease and its severity are largely influenced by host genetic factors, in addition to other virus- and host-related factors. In this study, we investigated the contribution of selected single nucleotide polymorphisms (SNPs) in innate immunity genes to predisposition to TBE in humans. More specifically, we investigated a possible association between SNPs rs304478 and rs303212 in the gene Interferon Induced Protein With Tetratricopeptide Repeats 1 (IFIT1), rs7070001 and rs4934470 in the gene Interferon Induced Protein With Tetratricopeptide Repeats 2 (IFIT2), and RIG-I (Retinoic acid-inducible gene I) encoding gene DDX58 rs311795343, rs10813831, rs17217280 and rs3739674 SNPs with predisposition to TBE in population of the Czech Republic, where TBEV is highly endemic. Genotypic and allelic frequencies for these SNPs were analyzed in 247 nonimmunized TBE patients and compared with 204 control subjects. The analysis showed an association of IFIT1 rs304478 SNP and DDX58 rs3739674 and rs17217280 SNPs with predisposition to TBE in the Czech population indicating novel risk factors for clinical TBE but not for disease severity. These results also highlight the role of innate immunity genes in TBE pathogenesis.
Keywords: interferony; Encephalitis, Tick-Borne; Humans; Encephalitis Viruses, Tick-Borne; přirozená imunita; lidé; Genotype; klíšťová encefalitida; Polymorphism, Single Nucleotide; genotyp; Interferons; viry klíšťové encefalitidy; Immunity, Innate; jednonukleotidový polymorfismus